Contratación y arbitraje internacionales - Méndez Silva, Ricardo (Doctrina Jurídica, 2010)
https://archivos.juridicas.unam.mx/www/bjv/libros/6/2776/1.pdf
Keywords: Arbitrage international; Arbitragem; Arbitraje; Arbitraje Comercial International; Arbitration; International commercial arbitration

Uluslararası Ticari Tahkim ve geçici hukuki koruma tedbirleri - Balkar, Süheyla (Galatasaray Üniversitesi, 2010)
Yargılama sürecinin yaratabileceği olumsuzluklardan hak arayan kişileri korumaya ve onlara hukuki güven ortamı sağlamaya yarayan geçici hukuki koruma tedbirleri tüm hukuk sistemleri açısından yargılamanın etkinliğinin teminatıdır. Devlet yargısında olduğu gibi, özellikle ticari uyuşmazlıklar açısından büyük önem taşıyan tahkim yargılamasında da bu tür tedbirlerin varlığına ihtiyaç gün geçtikçe artmaktadır. Çalışmamızda, uluslararası ticari tahkime konu olan uyuşmazlıklarda geçici koruma tedbirlerine hükmedebilme yetkisi, bu yetkinin sınırları ve bu tür tedbir kararlarının icrası meseleleri gerek mahkemeler gerekse hakemler açısından incelenmiştir. Interim relief or provisional measures may be as important as an award on the merits of any arbitration case. If the subject matter of the arbitration is not preserved, a long and costly arbitration procedure may just end up in learning at the time of execution of the award, that there is no substance right to enforce anymore. Consequently, the topic of provisional measures, in the understanding that they maintain the status quo of the arbitration, becomes of great relevance to all who may be involved in the arbitration world. Nonetheless, the topic of provisional measures, the powers to enforce them and even, the degree of court cooperation/intervention in such matters, varies from one country to another. Unfortunately, provisional measures in arbitration face several problems related to the lack of actual enforceability of the arbitrators? resolutions as well as to the good will of the parties to arbitrate and to grant the other parties enough securities that the subject matter of the arbitration will be executable.
Keywords: Arbitration; Geçici hukuki korumalar; Hukuksal korunma; Incompatibility; Koruma tedbirleri; Legal protection; Protection measures; Tahkim; Temporary legal protection; Uyuşmazlık

Différends entre investisseurs et État : Prévention et modes de règlement autres que l’arbitrage - Conférence des Nations Unies sur le Commerce et le Développement (CNUCED) (Publications des Nations Unies, 2010)
Keywords: Différends; Etat; Investisseurs; Modes de règlement; Prevention

Chapitre II. Le consentement à l’arbitrage, manifestation d’une volonté contenue - Diallo, Ousmane (Le consentement des parties à l'arbitrage international, 2010)

Le consentement des parties à l’arbitrage international - Diallo, Ousmane (International, 2010)
Mode juridictionnel privé de règlement des litiges, l’arbitrage offre une alternative à la saisine du juge. Qu’il soit interne ou international, l’arbitrage repose généralement sur le consentement des parties. C’est donc à juste titre que celui-ci a été qualifié de pierre angulaire de l’arbitrage. Effectivement, c’est sur ce consentement que la justice privée s’est longtemps appuyée pour justifier sa légitimité, revendiquer son autonomie et conquérir un nouvel espace de liberté. Solidement porté par le consentement qui lui sert de fondement, l’arbitrage n’a cessé de se développer au point d’apparaître de nos jours comme le mode normal de règlement des litiges du commerce international. On le dit particulièrement adapté au règlement de telle ou telle catégorie de litiges, manière d’affirmer sa vocation à étendre son emprise. Parvenu à l’âge adulte, c’est donc tout naturellement que l’arbitrage cherche à s’affranchir du caractère exceptionnel que lui imprime sa subordination au consentement, lequel apparaît de plus en plus comme un îlot de résistance à son expansion, sinon à son efficacité. Première étude d’ensemble sur la question, le présent ouvrage a le grand mérite d’exploiter au mieux la richesse qu’offre une approche comparative, non seulement pour retracer le rôle important joué par le consentement dans l’évolution de l’arbitrage, mais aussi, et surtout, pour mettre à nu les multiples tentatives en vue de son émancipation de la tutelle des parties. Il en résulte une éclipse momentanée du consentement, qui ravive les contestations de la compétence arbitrale et dévoile à nouveau sa subordination au consentement, facteur de légitimation par excellence de l’arbitrage. C’est dire que le consentement ne fait pas que survivre à ces assauts, il réussit même à prospérer. Autant de questions aussi brûlantes qu’actuelles, sur lesquelles cet ouvrage offre une analyse détaillée et des solutions originales.
Keywords: Arbitrage international; Arbitration; Droit privé; International arbitration; Litige; Règlement des différends

L’ordre juridique arbitral : réalité, utilité et spécificité - Gaillard, Emmanuel (McGill Law Journal, 2010)
L’ordre juridique arbitral existe-t-il ? S’il est perçu par les arbitres, souvent de manière intuitive mais très réelle, c’est qu’il existe. L’ordre juridique arbitral ne doit pas cependant être exclusivement conçu comme une représentation mentale du rôle des arbitres et de la source de leur pouvoir de juger. Il existe en tant que système de droit.

Enforcement of Arbitral Awards in Sub-Sahara Africa - Onyema, Emilia (Arbitration International, 2010)
As the world celebrated the fiftieth anniversary of the New York Convention in 2008 it became necessary to examine the enforcement regimes for arbitration awards in Sub-Sahara Africa. This article examines the provisions for the recognition and enforcement, and requirements for the setting aside of both domestic and international arbitral awards under the arbitration laws of OHADA member states, Nigeria and Sudan, as representative of the legal regimes in Sub-Sahara African countries. The New York Convention applies to Convention awards in half of the countries of Sub-Sahara Africa. It is therefore relevant to examine the requirements for the enforcement of non-Convention awards in those states that are members of the New York Convention, and also in those states that are not members of the New York Convention. Different arbitration laws and regimes apply in the three representative jurisdictions chosen for this comparative analysis and these are also representative of the legal regimes in those countries with arbitration laws in the region. Though a generally supportive tendency towards the enforcement of arbitral awards can be gleaned from the examination of some arbitration-related judgments, this article again highlights the importance for the remaining countries in the region yet to sign up to and implement the New York Convention to consider adopting it, and for more arbitration hearings to be held within the region.
Keywords: Africa; Arbitrage; Arbitragem; Arbitration; Enforcement of Arbitral Awards; Sub-Sahara

Chapter 42, Dissenting Opinions by Party-Appointed Arbitrators in Investment Arbitration - van den Berg, Albert Jan (Looking to the future: essays in international law in honor of W. Michael Reisman, 2010)
Dissenting opinions appear to have become an accepted practice in international arbitration. Th e current debate concentrates on their procedure, form, and content. Alan Redfern noted that “[a]t present, a generally relaxed attitude towards dissenting opinions seems to be taken not only by the arbitral institutions, but also by the arbitrators themselves … .” In this contribution, I would like to explore the cautionary note with which Redfern concluded his seminal article, namely, that the “[t]ime has perhaps come to inquire whether the present leniency towards dissenting opinions … has gone too far.” I propose to do so with respect to investment arbitrations because ade available publicly, particularly party-appointed arbitrators’ dissenting opinions.
Keywords: Arbitrage; Arbitration; Arbitrator; Dissenting opinion; Investment arbitration; Opinion dissidente